Functional insights into the role of seminal plasma proteins on sperm motility of buffalo - Codognoto, Viviane Maria [UNESP]; Yamada, Paulo Henrique [UNESP]; Schmith, Rúbia Alves [UNESP]; de Ruediger, Felipe Rydygier [UNESP]; Scott, Caroline [UNESP]; de Faria Lainetti, Patrícia [UNESP]; Brochine, Suzane [UNESP]; de Paula Freitas-Dell'Aqua, Camila [UNESP]; de Souza, Fabiana Ferreira [UNESP]; Oba, Eunice [UNESP] (Elsevier, 2018)
The objective of the present study was to describe the proteins from the seminal plasma of buffalo and correlate these proteins with sperm motility. Ejaculates from sixteen Murrah buffalo were used. Semen collection was performed by electroejaculation, and the ejaculate was evaluated by macroscopic (volume) and microscopic analysis (subjective motility and vigor, as well as sperm concentration). After the analysis, the samples were centrifuged (800g for 10 min and 10,000 for 30 min at 4 °C), and the supernatant (seminal plasma) was used to determine total protein concentration by the Bradford method. Based on total protein concentration, an aliquot (50 μg) was taken to conduct protein in-solution digestion for nano-LC–ESI-Q-TOF mass spectrometry analysis. Samples were divided into two groups, minimal (little sperm motility) and greater (typical sperm motility), based on non-hierarchical clustering considering motility and emPAI protein value. The data were analyzed by multivariate statistical analysis using principal component analysis (PCA) and partial analysis of minimum squares discrimination (PLS-DA). Forty-eight proteins were detected in the seminal plasma, and fifteen were common to two groups. There were six proteins that were significantly different between the groups. The main functions of proteins in seminal plasma were catalytic and binding activity. Spermadhesin protein, ribonuclease, 14-3-3 protein zeta/delta and acrosin inhibitor were in greater amounts in seminal plasma from the group with greater sperm motility; prosaposin and peptide YY were in greater amounts in the group with little sperm motility. The proteins detected in the greater motility group were correlated with sperm protection, including protection against oxidative stress, lipid peroxidation, protease inhibition and prevention of premature capacitation and acrosome reaction. In the group with little sperm motility, one of the identified proteins is considered to be an antifertility factor, whereas the function of other identified protein is not definitive. Results from the present study add to the knowledge base about the molecular processes related with sperm motility, and these findings can be used for determining potential markers of semen quality.
Keywords: Biomarker; Male; Proteomic; Sperm